\(x.y=\frac{x}{y}\Leftrightarrow x.y:\frac{x}{y}=1\Leftrightarrow\frac{x.y.y}{x}=1\Leftrightarrow y^2=1\Leftrightarrow\orbr{\begin{cases}y=1\\y=-1\end{cases}.}\)
Nếu y=1 thay vao x+y=xy ta có \(x+1=x\Leftrightarrow1=0\)(loại)
Nếu y=-1 thay vào x+y=xy ta có \(x-1=-x\Leftrightarrow x+x=1\Leftrightarrow2x=1\Leftrightarrow x=\frac{1}{2}\)
vậy y=-1 ,x=1/2
từ x.y=x:y suy ra x(y-1/y)=0 =>x=0 hoặc y=1 ,y=-1
Nếu x=0 suy ra y=0 (loại)
Nếu y=1 => x+1=x(loại)
Nếu y=-1 => x-1=-x suy ra x=1/2
Vậy x=1/2 và y=-1